PENGARUH PENERAPAN PERMAINAN KECIL TERHADAP KEBUGARAN JASMANI SISWA SD NEGERI 16 MARTAPURA: Permainan Kecil dan Kebugaran - ririn pramita; Putri Cicilia Kristina; Endie Riyoko (Jurnal Speed (Sport, Physical Education, Empowerment), 2023)
The problem in this study is the lack of maximum physical fitness of SD Negeri 16 Martapura students. The purpose of this study was to determine the effect of the application of small game exercises on the physical fitness of SD Negeri 16 Martapura students. The research method used in this study is an experimental method with the type of one group pretest-postest design. The research sample amounted to 20 people with total population technique. Data collection techniques were carried out with tests and measurements. The test instrument uses TKJI. The research data analysis technique used the paired sample t test. Based on the findings of the research results and analysis of research data, this study concluded that there was a significant effect of the application of small games on the physical fitness of Class V students of SD Negeri 16 Martapura because Thitung was greater than Ttabel (4.819> 1.729).